Fighting back: Is defamation law a double-edged sword for #MeToo victims?. Issue 2 (3rd July 2021) - Dee, Juliet
ABSTRACT: During the past half-century, countless women have been victims of sexual harassment, groping, and rape. When the #MeToo Movement gained momentum in October 2017, women who had victimized began to speak out. If women who were victims of sexual predators had not originally reported being raped but came forward as part of the #MeToo movement two or three decades later and the perpetrators denied it (in essence, accusing the victims of lying), their only legal recourse has been to sue the sexual predators for defamation. The law of defamation is a double-edged sword, however, because if victims use social media platforms to "name and shame" the men who raped them, the perpetrators have also sued their alleged victims for libel. This discussion examines the effectiveness of turning to defamation law as a means of redressing grievances in #MeToo cases, and also applies critical legal theory to these cases. In other words, if there is pervasive structural inequity in the legal system, meaning that perpetrators are often wealthy and powerful men who can easily afford attorneys' fees, can victims still prevail in court, or can wealthy and powerful perpetrators buy their victims' silence with non-disclosure agreements?